I ( n ) = ∫ 0 2 π sin 2 n x d x X = r = 1 ∑ ∞ ( 2 r r ) I ( r )
Given the above, find ⌊ 1 0 4 X ⌋
Notation:
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Did exactly the same
Oh! That is something new to me! Can anyone explain me about this?
I rather did using Beta function!
Log in to reply
I would like to add another hint , if i may :
∫ 0 2 π s i n m x ⋅ c o s n x d x = 2 ⋅ Γ ( 2 m + n + 2 ) Γ ( 2 m + 1 ) ⋅ Γ ( 2 n + 1 )
Did anyone consider this approach , by substituting m → 2 n , n → 0 in the formula provided above ?
Log in to reply
Yeah, my friend used this method to solve it.
Log in to reply
@Raghav Vaidyanathan – Yes , it is a nice method .
Best of Luck Raghav for JEE
Reduction formula is just recurrence using IBP. Just google Wallis reduction formula
Log in to reply
Oh k. Yes it is Wallis reduction formula. I know about it a little.
Actually you know what , using Walli's Reduction formulae is the best approach for this question since most JEE aspirants know these formulae by heart . I am not saying that using Beta function won't do any good, just that use it for more complex problems .
But it's still your choice of using it or not :)
Log in to reply
Oh, is it so? Thanks for that! I will keep that in mind!
Problem Loading...
Note Loading...
Set Loading...
Using reduction formula, we get: I ( n ) = 2 n 2 n − 1 I ( n − 1 ) , I ( 0 ) = 2 π ⇒ I ( n ) = ( 2 n ) ( 2 n − 2 ) ( 2 n − 4 ) . . . ( 2 ) ( 2 n − 1 ) ( 2 n − 3 ) ( 2 n − 5 ) . . . . ( 1 ) × 2 π ⇒ I ( n ) = ( 2 n n ) × 2 π × 2 − 2 n ⇒ ( 2 n n ) I ( n ) = 2 π × 2 − 2 n ⇒ ∑ r = 1 ∞ ( 2 r r ) I ( r ) = 2 π ( 4 1 + 1 6 1 + 6 4 1 + . . . . ) = 6 π = X ⇒ ⌊ 1 0 4 X ⌋ = 5 2 3 5